2020
DOI: 10.1111/jcmm.15168
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine decreases formation of myofibroblasts and excessive extracellular matrix production in an in vitro human corneal fibrosis model

Abstract: Acetylcholine (ACh) has been reported to play various physiological roles, including wound healing in the cornea. Here, we study the role of ACh in the transition of corneal fibroblasts into myofibroblasts, and in consequence its role in the onset of fibrosis, in an in vitro human corneal fibrosis model. Primary human keratocytes were obtained from healthy corneas. Vitamin C (VitC) and transforming growth factor-β1 (TGF-β1) were used to induce fibrosis in corneal fibroblasts. qRT-PCR and ELISA analyses showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…4 f and Additional file 1 : Figure SIVF). Previous studies showed that ACh exerts anti-fibrotic effects via downregulation of pro-fibrotic transforming growth factor TGF-β1 [ 31 , 32 ]. In our study, diabetes significantly increased TGF-β1 expression and this was significantly downregulated in db/db-ChAT-tg heart (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 f and Additional file 1 : Figure SIVF). Previous studies showed that ACh exerts anti-fibrotic effects via downregulation of pro-fibrotic transforming growth factor TGF-β1 [ 31 , 32 ]. In our study, diabetes significantly increased TGF-β1 expression and this was significantly downregulated in db/db-ChAT-tg heart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study showed that anti-ischemic agent trimetazidine, which improves myocardial glucose utilization, reduced cardiac apoptosis and fibrosis in the rat model of T2DM [ 49 ]. ACh has been shown to exert anti-fibrotic effects via downregulation of pro-fibrotic transforming growth factor TGF-β1 [ 31 , 32 ]. TGF-β1 induces signaling cascade to activate transcription factor Smad2 and Smad3, thus upregulating downstream genes that are involved in myofibroblast differentiation [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the culture, cells were either maintained as keratocytes or differentiated towards broblast or myo broblast lineages as described in the methods section. [26][27][28][29] Expression of ALDH1 was signi cantly increased for keratocytes in the TCP group when compared to both at and patterned collagen lms (Fig. 3a).…”
Section: Orientation and Viability In 2d Culturementioning
confidence: 94%
“…22,23,26 Cells cultured in 10 % FBS were referred to as broblasts and cells cultured in 10 % FBS with TGF-B and ascorbic acid were referred to as myo broblasts, in accordance with ndings in other studies. [27][28][29] Preparation of collagen surfaces…”
Section: Cell Culturementioning
confidence: 99%
“…Activated keratocytes are differentiated into fibroblasts and further matured into myofibroblasts . During the differentiation of fibroblasts to myofibroblasts, the expression of corneal Crystallin protein (aldehyde dehydrogenase class 3 (ALDH3)) and proteoglycans (lumican (LUM) and keratocan (KERA)) are reduced, but the expression of α-smooth muscle actin (α-SMA) and excessive disorganized extra-cellular matrix (ECM), such as collagen I and III, and fibronectin 1 (FN 1) , are increased. As a result, these changes contribute to corneal haze and reduced function of the cornea .…”
Section: Introductionmentioning
confidence: 99%